Analysis of Traditional Market Potential in Competition in the Digital Era of Tasikmalaya City - Andini, Dina; Kusnandar, Hasan Fahmi (Universitas Tanjungpura, 2026)
The aim of this research is to determine the potential of traditional markets in Tasikmalaya City in the digital era.The method used in this research is descriptive qualitative, by describing phenomena that occur in fact in the field. The data collection technique is by direct observation and interviews with consumers and traditional market traders. The next data were analyzed descriptively and qualitatively by presenting the data in a structured manner so that the researcher could obtain an overview of what was intended to be studied. NVivo 15 application was used as a tool to assist in data management and analysis. The results of this research are that the Tasikmalaya City traditional market has eight potentials : first, affordable price potential, second, product quality potential, third, moral potentian, fourth, market facility potential, fifth, service quality potential, sixth, product completeness potential, seventh, human resources potential of the Tasikmalaya City traditional market, and eighth, land potential. With these potentials, the traditional market of Tasikmalaya City will be able to compete in the current digital era. And it can increase the income of traders in the traditional markets of Tasikmalaya City. Market potential is one of the supporting factors in traditional market competition in the current digital era. Utilizing and maximizing the potential that exists in this market can increase people's income and encourage people to be independent and economically independent.